The Impact of Social Media Applications on Second Language Acquisition Among Adult ESL Learners of UOG - Dildar Ahmed; Dr. Raza-E-Mustafa; Iftkhar Ahmad (Journal of Peace, Development and Communication, 2024)
This paper aims to theoretically analyze how new online media, such as online texts, tests, learning materials, films, and music, impact L2 acquisition among Pakistani students. In today’s era of information, where quick but often unimportant information is constantly being distributed, it is crucial to examine the impact of such media on language learning, especially for non-native speakers. Through a questionnaire-based research study, the author intends to demonstrate online media’s positive and practical implications on L2 acquisition by Pakistani adult students’ proficiency levels. The study focuses on the influence of various online resources such as the Internet, social networking sites like Facebook and Twitter, and other potential stimuli. The study’s results are expected to show that the impact of online media on L2 acquisition by Pakistani students is significant and beneficial.